Peran Guru PAI Sebagai Motivator Pada Siswa SMPIT Ulil Albab Kota Batam - Ibtihal Istiqomah; Indah Muliati (KOLONI, 2024)
The role of Islamic Religious Education teachers as motivators in helping students' spiritual development is about honesty, patience, resilience, and teachers also help students understand and apply spiritual values such as responsibility and empathy. The purpose of this study is to find out the role of Islamic religious education teachers as motivators in helping spiritual development in students. This research is qualitative with the type of field study research. The subject of the research is an Islamic religious education teacher at SMPIT Ulil Albab, Batam City. Data collection techniques through interviews, observations, and documentation. The results of this study show that the role of Islamic religious education teachers as motivators in helping students' spiritual development is to provide direction, advice, encouragement and through positive habits that are always applied.